Tribological Evaluations of Polyester Composites Considering Three Orientations of CSM Glass Fibres Using BOR Machine - Yousif, B. F.; El-Tayeb, N. S. M. (SPRINGER, 2007)
In the current work, the effects of chopped strand mat ( CSM) glass fibre 450 g/ m(2) on tribo- properties of unsaturated polyester are evaluated. Experimental tests were performed by using Block on Ring ( BOR) machine against polished stainless steel under dry contact condition. Three principle orientations of CSM glass fibre in the matrix were considered, i. e. namely Parallel ( P- O), Anti- Parallel ( AP- O) and Normal ( N- O). Specific wear rate, friction coefficient and interface temperature were determined and presented as a function of applied load ( 30 - 100 N), and sliding distance ( 0 - 14 km) at two different sliding velocities ( 2.8 and 3.9 m/ s). Scanning electron microscopy ( SEM) was used to observe the damages features on the worn surfaces. The results showed that the orientations of CSM glass fibre significantly influenced the tribological performance of polyester composite. Better tribo performance were achieved when the polyester was reinforced with CSM glass fibre and tested at Parallel orientation. Moreover, specific wear rate and friction coefficient of polyester was reduced by 75%, and 55% at P- O of CGRP composite. The damage features were predominated by debonding of fibers, matrix deformation and polyester debris transfer.